Action of -Amanitin during pyrophosphorolysis and elongation by RNA polymerase II. - Chafin, D.R.; Guo, H.; Price, D.H. (Journal of Biological Chemistry, 1995)
Using defined elongation complexes formed on dC-tailed templates with Drosophila RNA polymerase II, we have examined elongation, pyrophosphorolysis, and DmS-II-mediated transcript cleavage and the inhibitory effect of alpha-amanitin on these processes. Analysis of pyrophosphorolysis on soluble or immobilized and templates confirmed that NTPs are liberated instead of dinucleotides that are released during DmS-II-mediated transcript cleavage. 10 microgram/ml alpha-amanitin completely inhibited DmS-II-mediated transcript cleavage but allowed extended pyrophosphorolysis and nucleotide addition to occur. alpha-Amanitin dramatically decreased the Vmax for nucleotide addition but only slightly affected the Km for nucleotides. Although the processes ae mechanistically distinct, both pyrophosphorolysis and DmS-II-mediated transcript cleavage frequently resulted in similar patterns of shortened transcript. Since polymerase molecules encounter similar kinetic barriers during both processes, it is possible that there is a common step in the reverse movement of the polymerase.